Budaya Organisasi dan Kepemimpinan Sebagai Determinan Kinerja Karyawan - Savanna Inggil; Rahayu Mardiana; Retno Widya Ningsih; Melly Marlinda; Qisthi Khoirunnisa; Pujianti Amalia; Winda Widiyanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aimed to examine the influence of organizational culture and leadership on employee performance in organizations located in North Cikarang District. A quantitative research approach with a survey method was employed involving 70 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The results revealed that organizational culture had a positive and significant effect on employee performance, with a path coefficient of 0.556, a t-statistic of 6.777, and a p-value of 0.000. Leadership also showed a positive and significant effect on employee performance, with a path coefficient of 0.269, a t-statistic of 2.706, and a p-value of 0.007. The R-square value of 0.425 indicates that organizational culture and leadership jointly explain 42.5% of the variance in employee performance. These findings highlight the importance of strengthening organizational culture supported by effective leadership practices to improve employee performance.